Efeito da progesterona na expressão do RNAm do receptor de LH e enzimas esteroidogênicas reguladoras do desenvolvimento folicular em células da granulosa de novilhas nelore - Dias, Henrique Pedro [UNESP] (2015)
The aim of this study was to investigate the effect of P4 concentration on the abundance of LHR mRNA and steroidogenic enzymes in granulosa cells of the dominant follicle (DF) in Nellore heifers. High progesterone negatively affects the expression of LHR and steroidogenic enzymes, providing lower follicular development. 52 Nellore heifers were pre-synchronized (D-17: BE + 2 mg intravaginal device CIDR® progesterone; D-10: 12.5 mg PGF2a Lutalyse®; D-8: 0.5 mg ECP® and withdrawal CIDR®). Heifers who responded to the pre-synchronization (presence of CL) underwent follicular ablation and blood collection on D0 and randomly divided into 6 groups: G1: High P4-D5 (implant CIDR1 (new) on D0 and slaughtered after 5 days); G2: Low P4-D5 (implant CIDR3 (previously used for 18 days) on D0 and 25mg PGF2a in D0 and D1, D5 slaughter); G3: High P4-D6 (implant CIDR1 and slaughtered after 6 days); G4: Low P4-D6 (CIDR3 implant in D0 and application of 25mg PGF2a in D0 and D1, slaughter D6); G5: High P4 + PE (proestrus) (CIDR1 implant in D0, CIDR, blood collection and application of 25mg PGF2a in D5 and slaughtered in D6); G6: Low P4 + PE (CIDR3 implant in D0 and application of 25mg PGF2a in D0 and D1, CIDR, blood collection and application of 25mg PGF2a on D5, slaughtered on D6). The ovaries were removed, the DF measured and dissected to obtain the granulosa cells. The plasma concentrations and intrafollicular P4, E2 and free IGF-1 were measured. Comparisons of the effect of lenght (G1 e G2 x G3 e G4), proestrus effect (G3 e G4 x G5 e G6) and the effect of P4 and their interactions on the LHR mRNA levels and steroidogenic enzymes were performed by ANOVA. Granulosa cells from DF exposed to higher concentration of P4 showed lower mRNA abundance of the LHR, aromatase and 3β-HSD (P <0.05). In conclusion, the high concentration of P4 leads to lower expression of LHR and 3β-HSD in granulosa cells independently ...